A novel method for routine quality assurance of volumetric‐modulated arc therapy. Issue 10 (25th September 2013) - Wang, Qingxin; Dai, Jianrong; Zhang, Ke
Abstract : Purpose: : Volumetric‐modulated arc therapy (VMAT) is delivered through synchronized variation of gantry angle, dose rate, and multileaf collimator (MLC) leaf positions. The delivery dynamic nature challenges the parameter setting accuracy of linac control system. The purpose of this study was to develop a novel method for routine quality assurance (QA) of VMAT linacs. Methods: : ArcCheck is a detector array with diodes distributing in spiral pattern on cylindrical surface. Utilizing its features, a QA plan was designed to strictly test all varying parameters during VMAT delivery on an Elekta Synergy linac. In this plan, there are 24 control points. The gantry rotates clockwise from 181° to 179°. The dose rate, gantry speed, and MLC positions cover their ranges commonly used in clinic. The two borders of MLC‐shaped field seat over two columns of diodes of ArcCheck when the gantry rotates to the angle specified by each control point. The ratio of dose rate between each of these diodes and the diode closest to the field center is a certain value and sensitive to the MLC positioning error of the leaf crossing the diode. Consequently, the positioning error can be determined by the ratio with the help of a relationship curve. The time when the gantry reaches the angle specified by each control point can be acquired from the virtual inclinometer that is a feature of ArcCheck. The gantry speed between two consecutive control points is then calculated. The aforementioned dose rate is calculated from an acm file that is generated during ArcCheck measurements. This file stores the data measured by each detector in 50 ms updates with each update in a separate row. A computer program was written in MATLAB language to process the data. The program output included MLC positioning errors and the dose rate at each control point as well as the gantry speed between control points. To evaluate this method, this plan was delivered for four consecutive weeks. The actual dose rate and gantry speed were compared with the QA plan specified. Additionally, leaf positioning errors were intentionally introduced to investigate the sensitivity of this method. Results: : The relationship curves were established for detecting MLC positioning errors during VMAT delivery. For four consecutive weeks measured, 98.4%, 94.9%, 89.2%, and 91.0% of the leaf positioning errors were within ±0.5 mm, respectively. For the intentionally introduced leaf positioning systematic errors of −0.5 and +1 mm, the detected leaf positioning errors of 20 Y1 leaf were −0.48 ± 0.14 and 1.02 ± 0.26 mm, respectively. The actual gantry speed and dose rate closely followed the values specified in the VMAT QA plan. Conclusions: : This method can assess the accuracy of MLC positions and the dose rate at each control point as well as the gantry speed between control points at the same time. It is efficient and suitable for routine quality assurance of VMAT.